2009
DOI: 10.1021/es8033439
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Nitrate-Induced Photodegradation of Chlorotoluron: Evidence of the Process in Aquatic Mesocosms

Abstract: The nitrate-induced photodegradation of chlorotoluron was demonstrated to occur efficiently in natural water through two series of experiments in outdoor aquatic mesocosms. During the first campaign, it was shown that the pesticide degradation kinetics was clearly dependent on nitrate concentration. This parameter also influenced the accumulation of the first- and second-generation byproducts, including predominantly N-terminus oxidation products and nitro-derivatives of the phenyl ring. The latter compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…While HA scavenged radicals as light-absorbing species and result in a quenching effect on the reaction system [33,38], so the higher of the HA concentration, the more evident of the inhibitory effects, which was consistent with the previous reports [19,39]. In contrast, a promoting effect of 10 mg/L NO 3 − on the photodegradation of CZ was discovered, which might be caused by the generation of nitrogen reactive species (NRS) and ROS from NO 3 − under the UV-254 nm [40,41]. However, 5 or 50 mg/L NO 3 − almost had no effects on the photodegradation of CZ, this was probable due to the insufficient of NO 3 − or the competitive photoabsorption by the high concentration of NO 3 − [19].…”
Section: Effect Of Ph On the Photodegradation Of Czsupporting
confidence: 88%
“…While HA scavenged radicals as light-absorbing species and result in a quenching effect on the reaction system [33,38], so the higher of the HA concentration, the more evident of the inhibitory effects, which was consistent with the previous reports [19,39]. In contrast, a promoting effect of 10 mg/L NO 3 − on the photodegradation of CZ was discovered, which might be caused by the generation of nitrogen reactive species (NRS) and ROS from NO 3 − under the UV-254 nm [40,41]. However, 5 or 50 mg/L NO 3 − almost had no effects on the photodegradation of CZ, this was probable due to the insufficient of NO 3 − or the competitive photoabsorption by the high concentration of NO 3 − [19].…”
Section: Effect Of Ph On the Photodegradation Of Czsupporting
confidence: 88%
“…The most reactive species is ·OH attacking C-H bonds in a relatively nonselective manner at diffusion-controlled rates, and it most likely participates in the photodegradation of pesticide. The photoinduced homolytic cleavage of the N-O bond in NO 3 − and NO 2 − producing ·OH was confirmed by formation of nitro and nitroso derivatives in the photolysis of chlortoluron 51) and monolinuron. 52) CO 3 −· is more selective than ·OH toward electron-rich S-and N-containing chemicals, 53) and the negative correlation of 55) These results show that the two anions act as a radical source and that CDOM has the dual character of a radical scavenger and a photo-sensitizer ( Fig.…”
Section: Photodegradation Of Pesticidementioning
confidence: 83%
“…Nélieu et al (2004) studied the photodegradation of monolinuron and found out that addition of nitrates increase the photodegradation of the compound. Shankar et al (2008) and Nélieu et al (2009) also observed faster photodegradation rates of several phenylureas in the presence of nitrates. Regarding the other two pH values, only monolinuron was decreased by 10% and 15% at pH 7 and 9, respectively (Fig.…”
Section: Substituted Urea Herbicidesmentioning
confidence: 85%